PENDAMPINGAN PENYUSUNAN SISPENA SEKOLAH DAN MADRASAH DALAM MENINGKATKAN MUTU AKADEMIK DI BAWAH NAUNGAN PC.LP MA’ARIF NU METRO - Masrurotul Mahmudah; Hernisawati Hernisawati; Andika Ari Saputra (STKIP Persada Khatulistiwa Sintang, 2022)
ABSTRACTAcademic quality in schools and madrasas greatly affects the learning quality of students and teachers' professionals in teaching. Improving academic quality in schools and madrasas requires accreditation from a team or assessor of the National Accreditation Board for Schools or Madrasah (BAN-S/M) in order to compile forms and improve the quality of these schools and madrasas. Accreditation of schools or madrasas functions for knowledge, namely in order to determine the feasibility and performance of schools and madrasas seen from various elements. Excellent schools and madrasas refer to the management of improving the quality of education personnel. The purpose of the Mentoring is to determine the feasibility of the academic quality of schools and madrasas and to know the system of developing school and madrasa forms in improving academic quality under the auspices of PC.LP Ma'arif NU Metro in Metro City. The author concludes that assistance in the preparation of the school and madrasa accreditation assessment system can improve academic quality under the auspices of PC.LP Ma'arif NU Metro', assistance in the preparation of the school accreditation assessment system through discussion group activities to improve the academic quality of schools under the auspices of Ma'arif Nahdlatul Ulama Educational Institution Branch Manager, Metro City, Lampung Province.Keywords: Academic Quality, Preparation of the National Education System, Schools and Madrasah.ABSTRAKMutu akademik di sekolah dan madrasah sangat mempengaruhi kualitas belajar peserta didik dan profesional guru dalam mengajar. Peningkatan mutu akademik di sekolah dan madrasah diperlukan adanya akreditasi dari tim atau asesor Badan Akreditasi Nasional Sekolah/Madrasah (BAN-S/M) guna penyusunan borang dan memperbaiki kualitas sekolah dan madrasah tersebut. Akreditasi sekolah atau madrasah berfungsi untuk pengetahuan, yaitu dalam rangka untuk mengetahui kelayakan serta kinerja sekolah dan madrasah dilihat dari berbagai unsur. Sekolah dan madrasah yang unggul mengacu pada manajemen peningkatan mutu tenaga kependidikan. Tujuan Pendampingan yaitu untuk mengetahui kelayakan mutu akademik sekolah dan madrasah serta mengetahui sistem pembinaan penyusunan borang sekolah dan madrasah dalam meningkatkan mutu akademik di bawah naungan PC.LP Ma’arif NU Metro di Kota Metro. Penulis mengambil kesimpulan bahwa pendampingan penyusunan pada sistem penilaian akreditasi sekolah dan madrasah dapat meningkatkan mutu akademik di bawah naungan PC.LP Ma’arif NU Metro’, pendampingan penyusunan pada sistem penilaian akreditasi sekolah melalui kegiatan grup forum diskusi untuk meningkatkan mutu akademik sekolah di bawah naungan Pengurus Cabang Lambaga Pendidikan Ma’arif Nahdlatul Ulama Kota Metro Provinsi Lampung.Kata Kunci: Mutu Akademik, Penyusunan Sispena, Sekolah dan Madrasah.